EFFECT OF POLAR STRATOSPHERIC CLOUDS ON GEOCHEMICAL CYCLE OF STRATOSPHERIC MATERIAL : STRATOSPHERIC PARTICLE PRECIPITATION - イワサカ, ヤスノブ; ハヤシ, マサヒコ; IWASAKA, Yasunobu; HAYASHI, Masahiko (National Institute of Polar Research, 1990)
P(論文) A numerical calculation was done to see the effect of particulate matter sedimentation formed in the stratosphere on transport of atmospheric sulfuric acid and nitric acid to the troposphere and near the ground. Extremely large particle formed in the Antarctic winter stratosphere can produce large flux of these acids from the atmosphere to the ground. departmental bulletin paper